Design and construction of a multi-input boost converter - Diffa, Allif Khairul; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2025)
This study designs and implements a Multi Input Boost Converter (MIBC) to improve the efficiency and stability of renewable energy systems. The device combines two DC voltage sources, such as solar panels and wind turbines, into a higher and more stable output voltage. The system is controlled by an Arduino Mega 2560 programmed via MATLAB Simulink to generate Pulse Width Modulation (PWM) signals, which are amplified by an IR2110 gate driver before activating the MOSFET. Two 12 V DC inputs are processed through the boost converter circuit to produce voltages of up to 24 V DC. An ACS712 current sensor and a voltage sensor are used as feedback for real-time duty cycle adjustment. The research process includes block diagram design, circuit construction, hardware assembly, and microcontroller programming. Testing on 50 Ω and 110 Ω loads shows that the MIBC can efficiently combine two power sources, maintain voltage stability, and minimize power losses. This design enhances the reliability and flexibility of hybrid power generation systems and has the potential to serve as a reference for developing multi-input power conversion in small to medium-scale renewable energy applications.